The Effect of Work Environment, Work-Life Balance, dan Burnout on Employee Performance (Case Study at PT. Pertamina (Persero) RU-VI Balongan - Ratu Sekar Langen Pujiwati; Nur Aisyah; Budi Agung Prasetya; Syaikh Maulana (Indonesian Journal of Business Analytics, 2024)
This study analyzes the effect of the work environment, work-life balance, and burnout on employee performance at PT. Pertamina (Persero) RU-VI Balongan. Using an explanatory survey method, this research involved 62 respondents. The analysis results indicate that the work environment and work-life balance significantly affect employee performance, while burnout does not have a significant effect. The study also found that these three variables simultaneously have a significant effect on employee performance. Recommendations for PT. Pertamina RU-VI Balongan include improving the quality of the work environment, maintaining work-life balance, and monitoring and managing employee burnout levels to enhance overall performance.